Pendekatan Active Learning Dalam Pembelajaran Bahasa arab di Pondok Modern Fathul Majid Kasiman Bojonegoro - Mohammad Makinuddin -; Friendis Syani Amrulloh (Balai Diklat Keagamaan Semarang, 2025)
This study examines the implementation of the active learning approach in Arabic language learning at Pondok Modern Fathul Majid Kasiman Bojonegoro. This case study aims to analyze the implementation process, identify supporting factors and challenges, and describe the impact of this approach on students’ engagement, motivation, and speaking skills. Data were collected through observations, interviews, and documentation over two months. The results show that active learning significantly increases students’ active participation, self-confidence, and intrinsic motivation. The success of the implementation is influenced by the creative role of teachers, a conducive pesantren environment, and the use of varied learning media. The main challenges include differences in students’ abilities, limited time, facilities, and the complexity of the Arabic language. This approach is effective in creating an interactive and meaningful learning atmosphere and is highly recommended to improve the quality of Arabic language learning in modern pesantren